The Design of Petilasan Gilanglipuro, Gilangharjo Village, District of Pandak, Bantul Regency - Amos Setiadi; Floriberta Binarti; Anastasya Diah Ayu Pitaloka (Journal of Innovation and Community Engagement, 2024)
Community service activities, located in Gilangharjo Village, district of Pandak, Bantul Regency, aimed to encourage the community to enhance tourist attraction through mentoring in the Gilanglipuro site design. The approach used in this activity was participatory which was elaborated in 3 stages, namely preparation, implementation, and utilization. The preparation stage involved coordination with the Tourism Office and the officials of Gilangharjo Village, as well as identification of village potential data carried out by the university in collaboration with partners. The implementation stage included surveys and focused group discussions (FGDs). The results of this stage in an agreed-upon design concept were expected to become the village icon and a unique tourist destination in the district of Pandak. The utilization stage involved using the activity results to support the development process of the tourist attraction. This community service activity included students’ participation in the Architectural Internship subject. It aligned with the Freedom of Learning Independent Campus (MBKM) concept and encouraged the achievement of the Bantul Regency Medium-Term Development Plan (RPJM), especially in the district of Pandak. The result of those activities was the architectural design of the Gilanglipuro heritage site that accommodated Yogyakarta's cultural values, particularly Bantul, as an area with the title of Bumi Mataram.